A network analysis of ego depletion and self-management in patients with epilepsy: differences across seizure frequencies - Yin, Xiaoxiao; Cheng, Jifang; Tian, Wenhao; Wen, Chunjie; Jiang, Shengbo; Xuan, Yejing; Feng, Xiuqin (Frontiers in Psychiatry, 2025)
BackgroundSelf-management is essential for epilepsy control, yet many patients struggle with it, partly due to ego depletion. The interaction between ego depletion and self-management remains poorly understood in this population. This study employed network analysis to examine the interplay between ego depletion and self-management in patients with epilepsy, and to compare network structures across seizure frequency groups.MethodsA total of 655 patients with epilepsy completed validated self-report measures assessing ego depletion and self-management. Symptom-level associations were examined using network analysis, focusing on central and bridging components. Network comparison tests were conducted to assess differences across seizure frequency groups.ResultsKey ego depletion symptoms such as “repeated unpleasant thoughts” and “memory difficulties” emerged as central nodes. “Urges to hit or smash things” and “uncontrollable temper” served as important bridge symptoms linking ego depletion and self-management. Among self-management dimensions, medication adherence and goal-setting were closely connected to depletion symptoms. No significant structural differences were found between patient subgroups based on seizure frequency.ConclusionBy identifying “urges to hit or smash things” and “uncontrollable temper” as central therapeutic targets, this study highlights the potential of network analysis in uncovering intervention opportunities that may be overlooked by traditional methods. Clinically, targeting these nodes through emotion regulation training could effectively disrupt the pathway to poor self-management in epilepsy patients, thereby improving both treatment adherence and overall quality of life.